Environmental migrants and social-movement participation. (January 2021) - Koubi, Vally; Nguyen, Quynh; Spilker, Gabriele; Böhmelt, Tobias
The displacement of people due to climatic changes (environmental migration) presents major societal and governance challenges. This article examines whether and how climate-induced rural-to-urban migration contributes to social-movement participation. We argue that the mainly forceful nature of relocation makes environmental migrants more likely to join and participate in social movements that promote migrant rights in urban areas. Using original survey data from Kenya, we find that individuals who had experienced several different types of severe climatic events at their previous location are more likely to join and participate in social movements. This finding has important policy implications. National and local authorities should not only provide immediate assistance and basic social services to environmental migrants in urban settings, but also facilitate permanent solutions by fostering their socio-economic and political integration in order to prevent urban conflict.